The Influence Of Female Directors, The Size Of The Board Of Directors And Digital Transformation On Environmental, Social, And Governance (ESG) Disclosure - Dwiana Sari, Novita; Rahim, Rida; Adrianto, Fajri (SEAN Institute, 2024)
This study aims to determine the influence of Female Director, Board of Directors Size and Digital Transformation on Environmental, Social, and Governance (ESG) disclosure. The research method used is a quantitative method. The data used in this study is secondary data in the form of financial statements from the website (www.idx.co.id) and the Refinitiv Eikon Database. The population in this study is all companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2023 period. The sample was selected from the purposive sampling method and obtained a sample of 41 companies from several criteria that have been set. The analysis technique used in this study is panel regression analysis with the help of EVIEWS version 10. The results of the analysis show that Female Directors have a significant positive effect on ESG disclosure. The size of the board of directors does not have a significant positive effect on ESG disclosure. Digital Transformation has a positive and significant influence on ESG disclosure. This research can contribute to adding literature related to additional considerations such as Female Director, Board of Directors Size and Digital Transformation for investors in evaluating the Company's potential.